2015
DOI: 10.1186/s13148-015-0071-7
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation differences between in vitro- and in vivo-conceived children are associated with ART procedures rather than infertility

Abstract: BackgroundWe, and others, have demonstrated previously that there are differences in DNA methylation and transcript levels of a number of genes in cord blood and placenta between children conceived using assisted reproductive technologies (ART) and children conceived in vivo. The source of these differences (the effect of ART versus the underlying infertility) has never been determined in humans. In this study, we have attempted to resolve this issue by comparing placental DNA methylation levels at 37 CpG site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
83
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(89 citation statements)
references
References 63 publications
1
83
0
1
Order By: Relevance
“…Across limited loci the three assisted conception groups exhibited marked differences from the natural conception group, supporting the view that there are subtle epigenetic changes in children from parents who sought fertility treatment, relative to those conceived naturally. Consistent with this tenet, 4 of the 18 candidate CpG sites altered in placental tissue from children born to fertile parents compared with infertile parents (27) are located in or near significant clusters of two imprinted genes, growth factor receptor-bound protein 10 (GRB10) and necdin (NDN). Clustering analysis recapitulates the hypomethylation of placental GRB10 CpG sites in bloodspots of ART children compared with fertile controls (27) but is not congruent with those reported for NDN.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…Across limited loci the three assisted conception groups exhibited marked differences from the natural conception group, supporting the view that there are subtle epigenetic changes in children from parents who sought fertility treatment, relative to those conceived naturally. Consistent with this tenet, 4 of the 18 candidate CpG sites altered in placental tissue from children born to fertile parents compared with infertile parents (27) are located in or near significant clusters of two imprinted genes, growth factor receptor-bound protein 10 (GRB10) and necdin (NDN). Clustering analysis recapitulates the hypomethylation of placental GRB10 CpG sites in bloodspots of ART children compared with fertile controls (27) but is not congruent with those reported for NDN.…”
Section: Discussionmentioning
confidence: 58%
“…Consistent with this tenet, 4 of the 18 candidate CpG sites altered in placental tissue from children born to fertile parents compared with infertile parents (27) are located in or near significant clusters of two imprinted genes, growth factor receptor-bound protein 10 (GRB10) and necdin (NDN). Clustering analysis recapitulates the hypomethylation of placental GRB10 CpG sites in bloodspots of ART children compared with fertile controls (27) but is not congruent with those reported for NDN. The discordance likely reflects differences in tissue-specific DNA methylation between peripheral blood and placenta.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…A recent study using cord blood and placentas collected from the children conceived by ART and naturally conceived children showed that the source of alteration in DNA methylation status is a result of ART procedures, rather than the underlying fertility of the parents (Song et al 2015). Hiura and coworkers proposed that imprinting disorders are a combination of heredity, senescent, COH, ART procedures and culture medium that potentiates the early onset of the diseases .…”
Section: Epigeneticsmentioning
confidence: 99%
“…One study has shown that in some infertile men perturbations in methylation may contribute to abnormal embryo development (Aston et al 2012). The possibility that some aspect(s) of infertility per se contributes to altered phenotype and/or epigenotype is open for consideration and further investigation (Song et al 2015).…”
Section: Discussionmentioning
confidence: 99%